The Role of Canadian Public Libraries in Facilitating Sustainable Lifestyles - Spiteri, Louise (Partnership, 2025)
The importance of sustainable lifestyles is addressed in two of the United Nation’s Sustainable Development Goals. Public libraries can play a significant role in providing information and resources to lead to positive behavioural actions to help mitigate climate change. The paper examined the resources and programs that thirteen public libraries in Canada offer to people interested in pursuing a zero-waste (ZW) lifestyle. Catalogue and descriptive records for resources and programs related to ZW were extracted from Canadian public libraries that represented each of the provinces and territories. Thematic analysis was conducted on 335 unique subject headings (167 in English, 168 in French) obtained from the bibliographic records of 207 titles, as well as on the titles and descriptions of 34 library programs. This analysis revealed that the library resources covered a span of 14 ZW behaviours or activities, including childcare, food preparation, environmental sustainability, waste reduction, and waste disposal. Through their programs and collections, public libraries can help make sustainable lifestyles more attainable to a greater number of people across different social, cultural, and demographic groups. Given the increasing importance of sustainable lifestyles to mitigate climate change, public libraries could consider how to expand and emphasize their sustainability collections, and particularly programming, to further strengthen and demonstrate their commitment to supporting sustainable lifestyles and practices.